Phylogenetic and ecological correlates of pollen morphological diversity in a Neotropical rainforest. (27th August 2020) - Mander, Luke; Parins‐Fukuchi, Caroline; Dick, Christopher W.; Punyasena, Surangi W.; Jaramillo, Carlos
Abstract: Morphology varies enormously across clades, and the morphology of a trait may reflect ecological function or the retention of ancestral features. We examine the tension between ecological and phylogenetic correlates of morphological diversity through a case study of pollen grains produced by angiosperms in Barro Colorado Island, Panama (BCI). Using a molecular phylogeny of 730 taxa, we demonstrate a statistically significant association between morphological and genetic distance for these plants. However, the relationship is non‐linear, and while close relatives share more morphological features than distant relatives, above a genetic distance of ~ 0.7 increasingly distant relatives are not more divergent in phenotype. The pollen grains of biotically pollinated and abiotically pollinated plants overlap in morphological space, but certain pollen morphotypes and individual morphological traits are unique to these pollination ecologies. Our data show that the pollen grains of biotically pollinated plants are significantly more morphologically diverse than those of abiotically pollinated plants. Abstract in Spanish is available with online material. RESUMEN: La morfología varía enormemente entre clados y la morfología de un carácter puede ser reflejo de una función ecológica o de la retención de características ancestrales. Comparamos la influencia ecológica y filogenética en la diversidad morfológica a través de un estudio de caso de granos de polen producidos por angiospermas en Isla de Barro Colorado, Panamá (BCI). Utilizando una filogenia molecular de 730 taxa, demostramos una asociación estadísticamente significativa entre morfología y distancia genética. Sin embargo, la relación es no lineal, y mientras que los parientes cercanos comparten más características morfológicas que los parientes lejanos, por encima de una distancia genética de ~ 0, 7 parientes cada vez más distantes no son más divergentes en sus fenotipos. Los granos de polen de plantas con polinización biótica y abiótica se sobreponen en el espacio morfológico, pero algunas morfologías polínicas son exclusivas a cada uno de los dos tipos de polinización. Nuestros datos muestran que los granos de polen de las plantas polinizadas por vectores bióticos son significativamente más diversos morfológicamente que aquellos con polinización abiótica.